Representasi Komunikasi Remaja dalam Film Dilan 1990 dan Pengaruhnya terhadap Citra Pariwisata Kota Bandung - Vanadia Putri Prameswari; Beryl Athalariq Ramadhan; Nazwa Natania Maulidya; Zaskia Alya Maura Alfia; Nur Syifaa Fazilatun Nisaa; Arsih Amalia Chandra Permata; Wiyata Wiyata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study explores the representation of teenage communication in the film Dilan 1990 and its impact on the image of Bandung as a tourist destination. Using a descriptive qualitative approach and open-ended questionnaires, the research analyzes patterns of interpersonal communication between characters and viewers' emotional responses. Findings reveal that Dilan’s character demonstrates a poetic, humorous, and confident communication style, while Milea exhibits a more reflective and expressive approach. The balance of verbal and nonverbal language in the film fosters emotional closeness between the audience and the characters. Additionally, the portrayal of Bandung with a romantic and nostalgic atmosphere enhances its visual appeal, shaping a positive perception of the city. Filming locations such as Milea’s House, Warung Bi Eem, and Buah Batu Street have become tourist attractions through film-induced tourism. These findings indicate that film can serve as a strategic medium in constructing destination imagery through emotional and symbolic representation.